The relationship between the communication styles utilized by PPLIC salespersons and the attitude of customers towards the preferred communication style. - Cobrado, Alanne Jesl M.
The study was designed by the proponents to determine the relationship between the communication styles utilized by PPLIC salespersons and the preferred communication style of the customers. Based on a research conducted by Sheth, the proponents categorized the communication styles into three: self-oriented, interaction-oriented and task oriented. The most dominant communication style utilized by PPLIC salespersons were identified as well as the most dominant communication style preferred by the customers. Questionnaires pertaining to the three aforementioned communication styles were disseminated and gathered by the proponents to measure and compare the attitude of both salespersons and customers. This served as a basis for the acceptance and rejection of the formulated hypotheses., The results showed a mismatch between the preferred communication style of customers and the utilized communication style of the sales agents. Most customers prefer salespersons who utilize an interaction-oriented communication style while only a minority of PPLIC sale-agents utilized this particular communication style. Most of the PPLIC salespersons were dominantly self-oriented when only a few customers preferred a self-oriented salesperson. It was also found out that gender was a factor which contributed to the preference of customers when it came to their last preferred communication style. Significantly, the study proved that there is a relationship between the utilized communication which could lead to a high or low possibility of product purchase.